The Valuing of Mathematics Learning in Schools: A Gendered Perspective - Tasos Barkatsas; Huk Yuen Law; Wee Tiong Seah; Ngai Ying Wong (International Journal on Emerging Mathematics Education, 2019)
In this article, gender differences in the valuing of mathematics by Hong Kong primary and secondary students have been investigated. The participants were 1081 upper primary school (Grades 5 and 6) and secondary school (Grades 8 and 9) students from various metropolitan Hong Kong schools. An Analysis of Variance (ANOVA) was conducted to investigate the existence of gender differences on a number of values components. Statistically significant differences between boys’ and girls’ valuing of mathematics learning were found on three of the nine components derived via a Principal Component Analysis (PCA).